A Quiet Revolution? Youth Perception of State and Church Ideology in Zaire - Romaldi, Christa (University of Ottawa (Canada), 2010)
This thesis focuses on the power struggle between Mobutu's administration and the Catholic Church as it played out in the realm of education. In particular, it focuses on how state ideology, meaning authenticity and Mobutism, pervaded education through textbooks and teaching materials in 1970s Zaire and how the Catholic Church attempted to resist state ideology through education as well. Discourse analysis was used to determine how state dogma and Church opposition were disseminated to youth via educational materials. Furthermore, I examine how and why youth responded to this power struggle through the examination of painting, music and literature created by the 1970s cohort as they aged. Again, discourse analysis is used to understand the meanings conveyed through the art. Youth, I argue, have rejected Mobutu and his ideologies and remain uncertain, perhaps even suspicious, of the Catholic Church's role in Zaire (Democratic Republic of the Congo).
Keywords: Religion, History of.; Geography.; Sub Saharan Africa Studies.